Development of a Universal Nutritional Screening Platform for Plastic Surgery Patients. Issue 7 (July 2017) - Roy, Melissa; Hunter, Paul; Perry, Julie A.; Cross, Karen M.
Abstract : Background: Plastic surgeons routinely see patients with complex or chronic wounds of all etiology. In a previous study, we found that up to 1 in 4 of these patients is at risk for malnutrition, which may be influencing their ability to heal. The goal of this study was to develop and validate a universal screening protocol that would be fast and accurate and allow for effective intervention and optimization of nutrition before plastic surgery. Methods: To accomplish these goals, we adopted a 2-part screening algorithm using the Canadian Nutritional Screening Tool (CNST) to triage patients in our outpatient clinics and then further screened those identified as being at risk using the Subjective Global Assessment (SGA) tool and blood work. Results: We screened 111 patients with diagnoses related to breast cancer (n = 10; 9.01%), elective surgery (n = 38; 34.23%), emergency surgery (n = 8; 7.21%), fractures (n = 15; 13.51%), and wounds (n = 40; 36.04%). Of the screened subjects, 15.32% (n = 17) were found to be at nutritional risk using the CNST, and 13 were confirmed to be moderately or severely malnourished using the SGA. Importantly, there were no positive correlations between nutritional status and smoking, diabetes, body mass index, or age, indicating that a universal screening protocol is needed to effectively screen a diverse plastic surgery population for malnutrition. Conclusions: Screening patients with both the CNST and the SGA is an effective way to identify patients before surgery to improve outcomes.